Interwar Labour Database, 1919-1944 [Canada] [Excel] - Statistics Canada (Borealis, 2000)
The Interwar Labour Database integrates early data to give as full a picture as possible of the economic conditions faced by Canadian workers from 1919 to 1944. During the period in question, four censuses provided labour information; in addition, monthly surveys were conducted by the Department of Labour, which gathered employment information from large employers and unemployment statistics from trade unions. The data series run from the start of 1919 to the end of 1944. The first date represents the beginning of monthly unemployment data, and is the earliest reasonable data for back-casting the employment series. The second date was chosen as the final year for two reasons: the Labour Force Survey (LFS) began the following year, and unemployment was essentially zero, owing to wartime conditions. The database covers all of Canada, except for Newfoundland, the Yukon and Northwest Territories. Data for Nova Scotia and Prince Edward Island are combined.